MiR-138 exerts anti-glioma efficacy by targeting immune checkpoints. Issue 5 (11th December 2015) - Wei, Jun; Nduom, Edjah K.; Kong, Ling-Yuan; Hashimoto, Yuuri; Xu, Shuo; Gabrusiewicz, Konrad; Ling, Xiaoyang; Huang, Neal; Qiao, Wei; Zhou, Shouhao; Ivan, Cristina; Fuller, Greg N.; et al.
Abstract: Background: Antibody therapeutic targeting of the immune checkpoints cytotoxic T-lymphocyte-associated molecule 4 (CTLA-4) and programmed cell death 1 (PD-1) has demonstrated marked tumor regression in clinical trials. MicroRNAs (miRNAs) can modulate multiple gene transcripts including possibly more than one immune checkpoint and could be exploited as immune therapeutics. Methods: Using online miRNA targeting prediction algorithms, we searched for miRNAs that were predicted to target both PD-1 and CTLA-4. MiR-138 emerged as a leading candidate. The effects of miR-138 on CTLA-4 and PD-1 expression and function in T cells were determined and the therapeutic effect of intravenous administration of miR-138 was investigated in both immune-competent and -incompetent murine models of GL261 glioma. Results: Target binding algorithms predicted that miR-138 could bind the 3′ untranslated regions of CTLA-4 and PD-1, which was confirmed with luciferase expression assays. Transfection of human CD4+ T cells with miR-138 suppressed expression of CTLA-4, PD-1, and Forkhead box protein 3 (FoxP3) in transfected human CD4+ T cells. In vivo miR-138 treatment of GL261 gliomas in immune-competent mice demonstrated marked tumor regression, a 43% increase in median survival time ( P = .011), and an associated decrease in intratumoral FoxP3+ regulatory T cells, CTLA-4, and PD-1 expression. This treatment effect was lost in nude immune-incompetent mice and with depletion of CD4+ or CD8+ T cells, and miR-138 had no suppressive effect on glioma cells when treated directly at physiological in vivo doses. Conclusions: MiR-138 exerts anti-glioma efficacy by targeting immune checkpoints which may have rapid translational potential as a novel immunotherapeutic agent.